The Impact of Skills Training on Cognitive Functioning in Older People with Serious Mental Illness: Results from a Randomized Controlled Trial - Pratt, Sarah I. (2013)
OBJECTIVES: Research on psychosocial interventions for people with serious mental illness (SMI) demonstrates that cognitive functioning is associated with psychosocial functioning. However, cognitive impairment is more pronounced and progressive in older adults with SMI and is associated with poorer functioning. Little is known about the long-term impact of psychosocial skills training on cognitive functioning in this rapidly growing group. DESIGN: We conducted post-hoc analyses on a previously reported randomized control trial to evaluate the relationship between cognitive and psychosocial functioning and the potential impact of psychosocial skills training on cognitive functioning over time. SETTING AND PARTICIPANTS: The current study was conducted using a community-dwelling sample of 183 people older than age 50 with SMI. INTERVENTION: Half of the study sample received a psychosocial skills training and health management program, Helping Older People Experience Success (HOPES), and were compared to a Treatment as Usual (TAU) group. MEASUREMENTS: Cognitive and psychosocial functioning were assessed at baseline and at 1-, 2-, and 3-year follow-up. RESULTS: Psychosocial functioning was strongly related to cognitive functioning at baseline. Participation in HOPES was not associated with greater improvements in overall cognitive functioning; however, exploratory analyses suggested a modest improvement in executive functioning. CONCLUSIONS: Given the lack of long-term data on interventions associated with sustaining or improving executive functioning in older adults with SMI, these exploratory findings suggest that future research is warranted to establish the potential benefit of psychosocial skills training as a component of treatment aimed at enhancing long-term psychosocial and cognitive functioning.